2018
DOI: 10.15283/ijsc17015
|View full text |Cite
|
Sign up to set email alerts
|

CD73, CD90, CD105 and Cadherin-11 RT-PCR Screening for Mesenchymal Stem Cells from Cryopreserved Human Cord Tissue

Abstract: Background and ObjectivesMesenchymal stem cells (MSCs) are self-renewing, non-specialized cells used clinically in tissue regeneration and sourced from bone marrow, peripheral blood, umbilical cord blood and umbilical cord tissue (UCT). To demonstrate an alternative method for MSC detection, cryopreserved UCT and expanded MSC were screened for MSC markers CD73, CD90, CD105 and CDH-11 by RT-PCR.Methods and ResultsHuman UCT were washed, sectioned, cryopreserved with 10% DMSO and stored in the vapor phase of liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The single connecting feature of all these tissues is the presence of perivascular space around the blood vessels where pericytes come off and differentiate into MSCs after vessels got inflamed or injured. According to their common origin, pericytes and MSCs both are negative for CD34, CD45, CD56 and positively express CD29, CD44, CD73, CD90, CD105, CD146 (5)(6)(7). MSCs are functionally defined based on their capacity to produce molecules that provide a regenerative and immunoregulatory milieu.…”
Section: Introductionmentioning
confidence: 99%
“…The single connecting feature of all these tissues is the presence of perivascular space around the blood vessels where pericytes come off and differentiate into MSCs after vessels got inflamed or injured. According to their common origin, pericytes and MSCs both are negative for CD34, CD45, CD56 and positively express CD29, CD44, CD73, CD90, CD105, CD146 (5)(6)(7). MSCs are functionally defined based on their capacity to produce molecules that provide a regenerative and immunoregulatory milieu.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the discovery of culture conditions dependent effects on surface marker expression, such as induction of SSEA-4 by fetal calf serum (5), and suppression of CD49f by confluency (6), further enhanced the ambiguity over MSCs identity. Pham et al showed that cryopreservation reduced the expression of CD73 (7). Lv et al articulated these issues in great detail in their recent review (8).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of gingival mesenchymal stem cells in this heterogeneous cell mixture was confirmed by fluorescent-activated cell sorting to detect the mesenchymal stem cell markers. The cultures significantly expressed CD73, CD90, and CD105, which are mesenchymal stem cell markers [32]. There was a low but detectable expression of CD44, an important activator of leukocytes [33].…”
Section: Discussionmentioning
confidence: 96%